PENGARUH KECENDERUNGAN CONSUMER ETHNOCENTRISM DOMESTIC PRODUCT BELIEF TERHADAP KEIGINAN UNTUK MEMBELI PRODUK ELEKTRONIK DI KOTA MATARAM, NUSA TENGGARA BARAT - Rusdan Rusdan; Baiq Ismiwati; Sulhaini Sulhaini; Rahman Dayani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
The main objective of the study was to examine the effect of consumer ethnocentrism toward domestic product belief and willingness to buy. The survey was carried out among students of the University of Mataram. A hundred of student sample were accidently determined during two weeks of data collection. Majority of them were students of the Faculty of Economic and Businesess. The study found that ethncentrism among students (young consumers) is still not really strong/medium level. This was seen also on domestic product belief and willingness to buy. Nevertheless, the tendency has a strong effect on domestic product belief and willingness to buy domestically made electronic products. This means it is important to strengthen the tendency among young (educated) consumers for the national economy.